The effect of three-minute exposure of oxygen plasma on the properties of tin oxide films - Е.А. Дмитриева; И.А. Лебедев; Е.А. Грушевская; Д.О. Мурзалинов; А.С. Серикканов; Н.М. Томпакова; А.И. Федосимова; А.Т. Темиралиев (Қарағанды университетінің хабаршысы. Физика сериясы)
Research devoted to the effect of three-minute exposure of oxygen plasma on the properties of tin oxide films investigation. The films were obtained by sol-gel method from five-water tin tetrachloride solution. The concentration of tin ions in the SnCl4/EtOH film-forming system was 0.14 mol/l. The solution system was deposed on the glass substrate by carring out a modified dipping method. Plasma treatment was performed at a pressure of 6.5 Pa and a power of about 20 Watts. The frequency of the oscillations produced by the generator was 27.12 ± 0.6 % MHz as well. The temperature of the samples during processing did not exceed 100 ºC. As a result of the formation of tin oxide (II), the film transmittance decreased after treatment with oxygen plasma. The width of the electric forbidden zone of the obtained samples was calculated, which was 3.95 eV for glass and 3.79 eV for film. The resistance of the films was determined by 10 measurements on different parts of the samples. The film without processing has a resistance of about 4255 ± 1158 kΩ, after processing, the resistance decreased by 25 times and amounted to 167 ± 26 kΩ. A decrease in resistance indicates an increase in the concentration of charge carriers in the sample. The resulting SnO is a semiconductor that lowers the transmittance of the studied films and contributes to reducing their resistance. X-ray structural analysis of the samples was also performed. After processing in oxygen plasma, the intensity of reflection from the (110) plane have increased. It should be noted that the number of planes with (101) indexes has decreased. The study of the sample surface showed the destructive nature of three-minute exposure by oxygen plasma.